The substantiation of the point that essential - Grygoryan, R.D.; Liabakh, E.G. (Reports of the National Academy of Sciences of Ukraine, 2014)
The substantiation of the point that essential arterial hypertension is organism’s protective response to the lack of ATP with the subsequent inhibition of metabolism in cells of various organs is given. Specific substances released by these cells activate parallel mechanisms supporting the ATP synthesis. One of these mechanisms is provided by cardiovascular system, Therefore, fluctuations or long-term shifts of blood pressure (BP) can serve as indicators of ways of compensation for ATP deficiency. Steady growth of BP indicates the reduced efficiency of other mechanisms maintaining the ATP synthesis.